Unlocking Bio-Based Potential: Assessing Biomass and Nutrient Availability for Sustainable Development - Emilija Mihajloska; Pavlina Zdraveva; Vladimir Gjorgievski; Natasa Markovska; Alajdin Abazi (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
This paper aims to offer actionable insights and recommendations for steering regions, particularly agricultural hubs, towards sustainable development in alignment with EU standards, while fostering resilience in the face of evolving challenges. A comprehensive survey with key stakeholders and detailed review of relevant national and local policies and documents were conducted in order to assess biomass and nutrient availability of Strumica region as a case study. The analysis identified primary agricultural and forestry residues, secondary residues from processing industries, and municipal biowaste as valuable resources. Furthermore, the paper highlights initiatives focusing on composting and mycelium-based products, emphasizing their environmental and economic benefits. Survey findings reveal the current state of waste management in processing industries and underscore the need for regulatory compliance and improved practices. Additionally, the paper examines nutrient availability in fertilizers and compost, stressing the importance of nutrient management in soil fertility and crop productivity. Recommendations include research on biomass utilization, policy support for modernization, promotion of composting practices, and collaboration with regional platforms.